Time setting of Konjaku monogatari-shū tales - M. V. Babkova (Шаги, 2022)
The article presents an analysis of the collection of Japanese Buddhist didactic tales (setsuwa) Konjaku monogatari-shū (early 12th century) in order to reconstruct the ideas of the compilers about time, their attitude to the endless flight of time and to the chain of events taking place in the world. All tales in Konjaku describe events that happened “a long time ago” and belong to history. So the readers look at what is happening with detachment, but within the stories time is either compressed or stretched out, creating a dramatic effect of presence. The tales in Konjaku are arranged in chronological order in the text as a whole and in its major parts. Sometimes some dates are given, but in and of itself this is not so important for the compilers. In some tales events follow each other very quickly, with no pauses. Or the action can go slowly, allowing readers to turn contemplative and to dispassionately follow what is taking place. The tales can also be divided into those that deal with a single episode in the life of the protagonist, those that describe his life as a whole, and those that tell of the lives of more than one generation of heroes. Stories about “causes and consequences” stand out. The narrator there directly focuses the attention of readers on the causal relationship between events. One of the main goals of the compilers of Konjaku is to show the readers the immutability of this connection and of the law of retribution. The article shows how the time setting of the tales and the treatment of time overall serve this purpose.